Effect of prevalent atrial fibrillation on cardiovascular outcomes in patients with chronic kidney disease. (25th November 2020) - Bhat, A; Gan, G; Chen, H.H.L; Gu, K; Denniss, M; Burgess, D.C; MacIntyre, R; Tan, T.C
Abstract: Background: The global increase in incidence and prevalence of chronic kidney disease (CKD) is associated with a parallel rise in co-morbid atrial fibrillation (AF). Concurrent presence of both conditions increases clinical complexity and may portend poor outcomes in this population. Purpose: The aim of our study was to assess the impact of prevalent AF on mortality and cardiovascular outcomes in patients with CKD. Methods: Consecutive patients with CKD (Stages 2 to 5) attending the Nephrology outpatient clinics in our health district between Jan 2007-Dec 2017 were retrospectively evaluated. Detailed appraisal of patient demographics, anthropometrics, clinical co-morbidities (including aetiology, stage and management of CKD) and pharmacotherapeutics was undertaken. These patients were followed for up to ten years for the composite outcomes of all-cause death and major adverse cardiovascular events (MACE). We excluded patients with incomplete clinical data and patients with concomitant medical co-morbidity limiting lifespan to <6 months. Results: 2008 patients (63.61±17.17 yrs; 55.7% men) were assessed. The mean eGFR was 37.53±21.88 mL/min/m 2 . Patients with prevalent AF (n=440, 22%) were older (p<0.01), with lower eGFR (p<0.01) and higher rates of renal replacement therapy (p<0.01). They also had a greater burden of coronary disease (p<0.01), heart failure (p<0.01), stroke (p<0.01), obstructive sleep apnoea (p<0.01), chronic obstructive pulmonary disease (p<0.01), anaemia (p<0.01) and obesity (p<0.01). Over the mean follow-up period of 44.04±34.96 months, 832 patients met the composite outcome (410 all-cause death, 422 MACE). On log rank tests, prevalent AF was a predictor of the composite outcome (Figure 1; p<0.01) and remained an independent predictor of all-cause death and MACE on multivariate analysis (HR 1.65; 95% CI 1.24–2.21, p<0.01). Conclusions: Prevalent AF is an independent predictor of all-cause death and MACE in patients with CKD. Funding Acknowledgement: Type of funding source: None